Research on co-spectrum sharing technology in LTE 2.1 GHz - Bei LI; Yuhua HU; Guanghai LIU; Tian XIAO; Chuntao SONG; Yi ZHANG; Bo WANG; Qunqing WANG (Dianxin kexue)
Spectrum sharing technology in 5G was introduced in the 3GPP standard.The types and principles of spectrum sharing were presented, the key factors for the realization of dynamic co-spectrum sharing were analyzed, the application configuration and suggestion for the implementation of dynamic co-spectrum sharing were presented, the effect of network application was verified, and the limitations of dynamic co-spectrum sharing in the existing network were summarized.